2012
DOI: 10.1016/j.aca.2012.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Layer-by-layer immobilization of carbon dots fluorescent nanomaterials on single optical fiber

Abstract: O PDF relativo ao artigo que solicita, não se encontra disponível em Acesso Aberto. Motivos: O editor não permite o depósito e disponibilização em acesso aberto do PDF que solicita. Para consultar o documento deve aceder ao endereço do editor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 21 publications
1
24
0
Order By: Relevance
“…It is very relevant in the case of optical fiber sensors because the Reprinted from [64] with permission from Elsevier substrate is made of glass, so that the losses due to refractive index change are reduced. On the other hand, the porous size can be adjusted to satisfy the specifications required by the final application depending on the reaction conditions.…”
Section: Sol-gel Matricesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is very relevant in the case of optical fiber sensors because the Reprinted from [64] with permission from Elsevier substrate is made of glass, so that the losses due to refractive index change are reduced. On the other hand, the porous size can be adjusted to satisfy the specifications required by the final application depending on the reaction conditions.…”
Section: Sol-gel Matricesmentioning
confidence: 99%
“…As an example of a fluorescent based optical fiber sensor, in Fig. 13.4 the response of the fluorescence emission peak as a function of the concentration of Hg + ions is shown [64].…”
Section: Multilayer Based Nanostructuresmentioning
confidence: 99%
“…The fiber optic probe could be reversibly detected in aqueous solution [20]. To modify this probe, they functionalized the CDs with PEG 200 and N-acetyl-l-cysteine [21]. Then the CDs could immobilize in the tip of an optical fiber using the layer-by-layer deposition method, resulting in an increase in sensibility of the fluorescent probe.…”
Section: Mercury (Ii) Ion Detectionmentioning
confidence: 99%
“…They can absorb ultraviolet or visible light for ten minutes, and then can emit light continually for more than ten hours after removal of excitation resource [7,8]. Such functional fibers can be used for technical textiles such as decorations, protections and medical textiles etc [5,[9][10][11]. However, few studies have been found about using chelating reaction method to fabricate AECC fibers.…”
Section: Introductionmentioning
confidence: 99%